Engagement with Mathematics: The Influence of Teachers - Catherine Attard (SEAMEO Regional Centre for QITEP in Mathematics, 2011)
Recent decades have seen growing concern over the lowering levels of engagement with mathematics in Australia and internationally. This paper reports on a longitudinal study on engagement with mathematics and explores the influences of teachers on the students’ engagement with mathematics. Findings reveal that the development of positive pedagogical relationships between students and their teachers forms a critical foundation from which positive engagement can be promoted.